Performance Quality of Braided e-Yarns for Pedestrian Interactive Textiles - Raphael Kanyire Seidu; Shouxiang Jiang (Engineering Proceedings)
A low-cost electronic yarn (e-yarn) fabricated with conductive yarns and light-emitting diodes (LEDs) for wearables is presented. As part of ongoing research to develop smart interactive pedestrian clothing, this work demonstrates the design and performance qualities of braided e-yarns to produce red lighting effects. The design process adopted a simple encapsulation process with adhesive tape and a heat contraction tube to secure stainless steel conductive threads to solder pads of the LEDs. These were arranged in series against two stainless steel conductive threads to provide single positive and negative terminals at both ends. The success of these low-cost, flexible, and strong (wash durability) braided e-yarns proved to be a major achievement for integration into woven fabrics for smart pedestrian safety clothing. These braided e-yarns producing the necessary lighting effects are a key safety feature for improving pedestrian visibility and driver recognition at night-time.